Proceedings of the Third UN/ESA/NASA Workshop on the International Heliophysical Year 2007 and Basic Space Science National Astronomical Observatory of Japan - Haubold, Hans J.; Mathai, A.M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book represents Volume II of the Proceedings of the UN/ESA/NASA Workshop on the International Heliophysical Year 2007 and Basic Space Science, hosted by the National Astronomical Observatory of Japan, Tokyo, 18 - 22 June, 2007. It covers two programme topics explored in this and past workshops of this nature: (i) non-extensive statistical mechanics as applicable to astrophysics, addressing q-distribution, fractional reaction and diffusion, and the reaction coefficient, as well as the Mittag-Leffler function and (ii) the TRIPOD concept, developed for astronomical telescope facilities. The companion publication, Volume I of the proceedings of this workshop, is a special issue in the journal Earth, Moon, and Planets, Volume 104, Numbers 1-4, April 2009.
Under Scrutiny -- Some Remarks on the Paper (3z(BOn the -type Distributions(3y (B-- Canonical Formulation of Fractional Kinetics -- Out-of-Equilibrium Statistical Mechanics in a Hamiltonian System with Mean-Field Interaction -- An Alternative Method for Solving a Certain Class of Fractional Kinetic Equations -- Extended Reaction Rate Integral as Solutions of Some General Differential Equations -- Solutions of the Fractional Reaction Equation and the Fractional Diffusion Equation -- Astrophysical Applications of Fractional Calculus -- Generalized Mittag-Leffler Distributions and Processes for Applications in Astrophysics and Time Series Modeling -- Solar Wind Speed Theory and the Nonextensivity of Solar Corona -- Dynamism in the Solar Core -- How the Literature is Used A View Through Citation and Usage Statistics of the ADS -- Photometric and Spectroscopic Studies of BW Eri -- Near Infrared Excess Energy in Binary System V367 Cygni -- Period Study and Secondary Maximum of KZ Hya -- Current and Future Capabilities of the 74-inch Telescope of Kottamia Astronomical Observatory in Egypt.s
Keywords: Physics; Mathematical physics; Astrophysics; Physics; Extraterrestrial Physics, Space Sciences; Mathematical Methods in Physics; Astrophysics and Astroparticles